Periclimenaeus devaneyi sp. nov., from Oahu, Hawai'i (Crustacea: Decapoda: Pontoniinae) - Bruce, A. J. (Zootaxa, 2010)
A new species of Periclimenaeus, P. devaneyi sp. nov, is described from Oahu, Hawai’an Islands. The new species is closely related to P. minutus and P. jeancharcoti, but can be distinguished from both species by the lack of transverse corrugations on the ungui of the ambulatory dactyls, and the absence of minute denticles on the corpus of the dactyli.